Evaluation of presence of a putative multidrug efflux pump gene (norM) in Leptospira spp. strains from bovine origin - Malliagros, L. V.; Correia, L.; Pires, B. C.; Brasil, T.; Carvalho-Costa, F. A.; Jaeger, L. H.; Lilenbaum, W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis in livestock is associated with large economic losses. In order to minimize these losses, different control strategies have been applied, including antibiotic therapy. Besides, failure of antibiotic therapy may be related to reduced susceptibility and the presence of genes associated with antimicrobial resistance.